ANALYSIS OF COGENERATION ENERGY CONVERSION SYSTEM DESIGN IN IPWR REACTOR - Ign. Djoko Irianto; Sriyono Sriyono; Sukmanto Dibyo; Djati Hoesen Salimy; Tukiran Surbakti; Rahayu Kusumastuti (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2022)
The acceleration of national development, especially in the industrial sector, requires an adequate national energy supply. There are various types of energy sources which include conventional energy sources as well as new and renewable energy sources including nuclear energy. The problem is how to utilize these energy sources into energy that is ready to be utilized. BATAN as a research and development institution in the nuclear field has taken the initiative to contribute to the development of technology for providing electricity and other thermal energy, particularly reactor technology as a power plant and a provider of thermal energy. This research aims to analyze the design of the IPWR type SMR reactor cogeneration energy conversion system. The IPWR reactor cogeneration energy conversion system which also functions as a reactor coolant is arranged in an indirect cycle configuration or Rankine cycle. Between the primary cooling system and the secondary cooling system is mediated by a heat exchanger which also functions as a steam generator. The analysis was carried out using ChemCAD computer software to study the temperature characteristics and performance parameters of the IPWR reactor cogeneration energy conversion system. The simulation results show that the temperature of saturated steam coming out of the steam generating unit is around 505.17 K. Saturated steam is obtained in the reactor power range between 40 MWth to 100 MWth. The results of the calculation of the energy utilization factor (EUF) show that the IPWR cogeneration configuration can increase the value of the energy utilization factor up to 91.20%.